(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Every nation has accepted or approved a game as their national game. Basically is the national game of Amenica; Cricket it is national game of United Kingdom like wise India also might have accepted or approved a game as the national game. Then what is that? Is it field hockey, or Kabaddi or chess or some other?